Cross-sectional study of Leptospira spp. in commercial pig farms in the state of Goiás, Brazil - Petri, Fernando Antônio Moreira [UNESP]; Sonalio, Karina [UNESP]; de Souza Almeida, Henrique Meiroz [UNESP]; Mechler-Dreibi, Marina Lopes [UNESP]; Galdeano, José Vanderlei Burim; Mathias, Luís Antônio [UNESP]; de Oliveira, Luís Guilherme [UNESP] (Springer Nature, 2021)
Leptospirosis is an infectious, contagious disease highly important to the world pig industry, which causes reproductive loss in breeding herds. Endemic infections in a herd may produce little evidence of clinical disease despite resulting in economic losses. However, some epidemiological features of leptospirosis in midwestern Brazil, such as risk factors and prevalence of the disease, remain unclear. Therefore, this study focused on assessing the prevalence of the Leptospira spp. in intensive pig herds and associating its risk factors. A set of 900 blood samples, equally distributed between nursery, growing, and finishing pigs of 30 intensive farrow-to-finish farms, were analyzed using the microagglutination test (MAT), in order to detect anti-Leptospira spp. antibodies for 24 different Leptospira spp. serovars. An occurrence of 4.67% (55/342) seropositive samples were detected in fattening pigs. The variables associated with the disease occurrence were animals per square meter at fattening (OR 0.006, CI 95% 0.004–0.42, p = 0.0105) and pen division between growing and fattening pigs (OR 3.56, CI 95% 0.563–22.541, p = 0.185). Thus, the variables semi-hollow floor in the maternity (OR 16.66; CI 95%: 2.17–128.2 and p = 0.006) and animals per trough at fattening (OR: 0.08, CI 95% 0.009–0.87 and p = 0.025), observed in this study, highlight the importance of the fattening phase in the epidemiology of the disease, bringing information on risk factors involved in the occurrence and dissemination of leptospirosis in intensive pig herds.
Keywords: Antibodies; Epidemiology; Leptospira spp; risk factors; Swine